Estudio de la calidad bacteriológica de doce plantas medicinales procesadas en la planta piloto de farmacia de la Universidad Técnica de Machala. - Barros Navarrete, Katherine Estefanía (2015)
This research work was conducted in the Academic Unit of Chemistry and Health at the “Universidad Técnica de Machala” (UTMACH). The purpose was to conduct a study of bacterial content of twelve medicinal plants commonly used, which were processed in the Pilot Laboratory of Pharmacy of that institution, and were sold in the central market of Machala city, except moringa which is grown in the backyards of Academic Unit of Agricultural Sciences of the same University.